Factores de riesgo, su desencadenamiento en las infecciones respiratorias agudas en niños menores de 5 años, ciudadela Sol Brisa 2 Cantón Babahoyo, Los Ríos, periodo septiembre 2017 a febrero 2018 - Figueroa Pincay, Karla Ximena (2018)
Acute respiratory infections (ARI) are a complex group of diseases caused by various causative agents that affect any point of the respiratory tract. They are one of the first causes of morbidity given worldwide in children under 5 years old. the various risk factors citadel Sol Brisa 2 Cantón Babahoyo, Los Ríos, period September 2017 to February 2018. In which field research was applied, by means of a survey to determine the predisposing factors of these infections, but the main one is the ignorance that mothers have about this issue, the fear that their son is sick makes them apply myths in the children with acute respiratory infections, therefore changing their habits, habits and attitudes is very difficult but educating about the prevention of acute respiratory infections in children